PERKEMBANGAN POPULASI Elaeidobius kamerunicus FAUST PASCA INTRODUKSI DAN PENINGKATAN FRUIT SET KELAPA SAWIT DI PULAU SERAM, MALUKU, INDONESIA - Agus Eko Prasetyo; Agus Susanto (Jurnal Penelitian Kelapa Sawit, 2016)
Elaeidobius kamerunicus is the main pollinating agent in oil palm plantations in Indonesia today. The development of oil palm plantations in new areas requires introduction of these insects, moreover the new areas are located on different islands. First introduction of Elaeidobius kamerunicus Faust had been done from North Sumatra to Seram Island on 23 September 2013. The introduction was performed on larva and pupa stadium in 4-5 days post anthesising of male inflorescences. The introduction of E. kamerunicus using plywood boxes has an average risk of death by 7.89% at 6 days delivery period. Observation before releasing of the weevils showed that this insect was not detected in both of oil palm male and female flowers and the oil palm fruit set was very low approximately 11.27%. For about 500 weevils/ha were released in Marnuhu estate and could be developed into 362,401 weevils/ha in 5 months with 97.86% of oil palm sex ratio. The oil palm fruit sets were increased after 1 and 2 months introduction, 53.70% and 75.56 %, respectively. The lower sex ratio of oil palm or the more availability of male inflorescences make growth of E. kamerunicus population became faster and the greater number of weevils that visiting anthesising of female flowers make the higher value of oil palm fruit set.